Reflective bistable cholesteric/polymer dispersion display with a black polypyrrole electrode cast from the solution - Kim, YC; Lee, JY; Pak, SS; Kim, CY (GORDON BREACH SCI PUBL LTD, 1999)
A reflective mode bistable cholesteric/polymer dispersion(CPD) display is proposed in which both the electrode and the light-absorbing layer of the conventional display were substituted with a single polypyrrole(PPy) layer spin-cast from the chloroform solution. Utilization of the black conductive PPy film coated on the inner surface of the rear glass plate not only provided a convenient and economic method of fabricating CPD displays but also improved the contrast ratio by about 20%. By incorporating 20% of polymer into the chiral nematic mixture, the bistability and the viewing angle of the display were remarkably enhanced while the reflectance decreased from 89 to 29%.